An assessment of exercises in biology workbooks - Vranova, Olga (e-Pedagogium, 2005)
The paper reports the results of an assessment of exercises in biology workbooks. Twelve workbooks were evaluated (published by Prodos, Fortuna, Nova skola and Jinan). Tollingerova's classification was implemented to assess the quality of the exercises. Results indicate that the least difficult exercises (groups 1 and 2) prevail in individual workbooks.
Keywords: Biology workbooks; type of exercises; exercise evaluation